Characterization of [18F]FPyKYNE-Losartan as a Novel PET Tracer for Imaging AT1 Receptors - Hachem, Maryam (Université d'Ottawa / University of Ottawa, 2015)
The Angiotensin II Type I Receptor (AT1R) is the main receptor that produces most of the physiological actions of the Renin Angiotensin System (RAS). Alterations of AT1R expression in renal and cardiovascular diseases make this receptor an attractive target for developing an imaging agent to monitor its expression in disease states. [18F]FPyKYNE-Losartan has been developed as a derivative of the clinically used AT1R blocker Losartan. The aim of this work was to characterize this tracer and evaluate its potential as an imaging agent for AT1Rs, thereby, progressing towards human imaging of the AT1R. MicroPET imaging in rats and PET imaging in pigs displayed specific AT1R binding, high kidney-to-blood and image contrast, and slow clearance from kidneys. [18F]FPyKYNE-Losartan was shown to have 2 types of labeled metabolites in rat plasma and kidneys: hydrophilic and hydrophobic, whereas, only hydrophilic metabolite(s) in pig plasma. Plasma protein binding of [18F]FPyKYNE-Losartan was determined, by an in vitro ultrafiltration method, to be 97% which is very similar to that of Losartan (98%). FPyKYNE-Losartan displayed full antagonism of Ang II pressor effect in rats in vivo, with an ED50 of 25.5 mg/Kg and 4-times (25%) less potency than Losartan. In vitro binding studies confirmed the binding selectivity of [18F]FPyKYNE-Losartan. Bmax and Kd parameters were determined to be 348 ± 112 fmol/mm2 and 49.4 nM, respectively. Rat dosimetry studies exhibited that the sex averaged effective doses of [18F]FPyKYNE-Losartan according to ICRP 60 and 103 protocols are 2.97E-02 (mSv/MBq) and 3.06E-02 (mSv/MBq), respectively, which are within an acceptable range compared with other F-18 labeled tracers and within the safety limits of the FDA. In conclusion, [18F]FPyKYNE-Losartan has an excellent potential for translation towards human imaging to monitor AT1R expression and guide therapy.
Keywords: Angiotensin II Type 1 Receptor; AT1R; RAS; [18F]FPyKYNE-Losartan; Losartan; PET; Metabolites; Antagonism; Binding selectivity; Dosimetry